Development and Evaluation of the Boston University Osteoarthritis Functional Pain Short Form (BU-OA-FPS). Issue 8 (19th April 2018) - Goode, Adam P; Ni, Pengshend; Jette, Alan; Fitzgerald, G Kelley
Abstract: Background: Pragmatic studies have gained popularity, thus emphasizing the need for patient-reported outcomes (PRO) to be integrated into electronic health records. Objective: This study describes the development of a customized short form from the Boston University Osteoarthritis Functional Assessment PRO (BU-OA-PRO) for a specific pragmatic clinical trial. Methods: A Functional Pain Short Form was created from an existing item bank of deidentified data in the BU-OA-PRO. Item response theory (IRT) methods were used to select items. Reliability was measured with the Cronbach alpha, then with IRT simulation methods. To examine validity, ceiling and floor effects, correlations between the short-form scores and scores from the BU-OA-PRO and the Western Ontario McMasters University Osteoarthritis Index (WOMAC) Pain and Difficulty subscales, and the area under the curve (AUC) were calculated. A minimum detectable change at 90% confidence (MDC90) was calculated based on a calibration sample. Results: The BU-OA-PRO was reduced from 126 items to 10 items to create the BU-OA Functional Pain Short Form (BU-OA-FPS). The Cronbach alpha indicated high internal consistency (0.91), and reliability distribution estimates were 0.96 (uniform) and 0.92 (normal). Low ceiling effects (4.57%) and floor effects (0%) were found. Moderate-to-high correlations between the BU-OA-PRO and BU-OA-FPS were found with WOMAC Pain (BU-OA-FPS = 0.67; BU-OA-PRO = 0.64) and Difficulty (BU-OA-FPS = 0.73; BU-OA-PRO = 0.69) subscales. The correlation between the BU-OA-PRO and BU-OA-FPS was 0.94. The AUC ranged from 0.80 to 0.88. The MDC90 was approximately 6 standardized points. Conclusions: The BU-OA-FPS provides reliable and valid measurement of functional pain. Pragmatic studies may consider the BU-OA-FPS for use in electronic health records to capture outcomes.